Preparation method of polysulfide ionic conductor

Through the rapid polymerization of polysulfide and comonomer, the preparation process of polymer ion conductors is simplified, the problems of complex process and difficult performance regulation in the existing technology are solved, and the preparation of efficient and green polysulfide ion conductors is achieved. , has stretchability, self-healing, good mechanical properties and electrical conductivity.

CN119192578APending Publication Date: 2024-12-27BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311102681.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The synthesis steps of existing polymer ion conductors are complicated and the preparation process is complicated, which is difficult to meet the needs of green manufacturing. The structure and performance of polysulfide functional materials are limited, and they cannot take into account flexibility, safety and raw material costs, and it is difficult to accurately regulate machinery. Strength and conductivity.

Method used

The rapid polymerization of polysulfide and comonomer is adopted to coordinate the molecular weight, flexibility, glass transition temperature and other characteristics of the ionic conductor through the coordinated regulation of the molecular weight, flexibility, glass transition temperature of the ionic conductor, lithium salts and ionic liquids regulate ionic conductivity, and crosslinkers regulate mechanical properties. ,实现无溶剂或室温溶液条件下的聚合,简化制备流程。

Benefits of technology

It realizes efficient preparation of stretchable and self-healing polysulfide ion conductors, with adjustable performance, simplified the preparation process, meets green chemistry requirements, improves mechanical properties and conductivity, and is suitable for a variety of ionic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004421195540000021
    Figure BDA0004421195540000021
  • Figure BDA0004421195540000051
    Figure BDA0004421195540000051
  • Figure FDA0004421195530000011
    Figure FDA0004421195530000011
Patent Text Reader

Abstract

The invention discloses a preparation method of a polysulfide ionic conductor, which efficiently generates ionic conductors with various performances and complex structures through rapid polymerization of polysulfide, and overcomes the contradiction between the complex structure and efficient manufacturing in a polymer ionic conductor. The mechanical property and conductivity of the polysulfide ionic conductor are regulated and controlled by utilizing a copolymerization strategy, the ionic liquid and the lithium salt, the comonomers involved in the invention are rich in variety, the generated polymer is diversified in structure and adjustable in performance, synchronous improvement of the mechanical property and the ionic conductivity in the ionic conductor is realized, and the polysulfide ionic conductor can be suitable for various ionic electric devices. The scheme is simple in process and high in atom utilization rate, meets the requirements of green chemistry, and has practical industrial feasibility. The polysulfide ionic conductor has abundant dynamic covalent bonds (such as disulfide bonds) and non-covalent interactions (such as hydrogen bonds and lithium bonds), so that the synthesized ionic conductor can be self-repaired, degraded and recycled, and the service life and life cycle of the material are prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention discloses a method for preparing a stretchable, self-repairing polysulfide ion conductor. Background technology:

[0002] Through molecular chain structure design, safe, flexible, and stretchable polymer ion conductors have acquired multiple functions such as transparency, biocompatibility, self-healing, and biodegradability, which have attracted widespread attention in the fields of ion electrical devices and human-computer interaction. The Center for Excellence in Nanoscience of the Chinese Academy of Sciences synthesized a dry ion conductive elastomer with a dynamic cross-linked structure. The ion conductor was prepared by Schiff base reaction of amino-terminated PEO and has the characteristics of self-healing, transparency, stretchability, and high conductivity (Adv. Mater. 2021, 33, 2101396). Michigan State University used soy protein to synthesize a new type of solid electrolyte, which was prepared from commercially available soy protein and hyperbranched polyimide (Adv. Sci. 2022, 9, 2103623). However, the synthesis steps of the above-mentioned ion conductors are cumbersome, the preparation process is complex, and the process is long, which makes it difficult to meet the industrial needs of green manufacturing. There is an urgent need for an efficient, pollution-free, and easy-to-promote method to prepare high-performance and multifunctional polymer ion conductors.

[0003] Using the dynamic disulfide bonds of polysulfides to construct functional materials is a new research hotspot. A variety of high-performance and multifunctional new polymer materials have been reported (Nat. Chem., 2013, 5, 518-524; Polym. Chem., 2018, 9, 2290-2294; Sci. Adv., 2018, 4, eaat8192). However, the current polysulfide functional materials are mainly polysulfide homopolymers, which have limited structure and performance, and cannot take into account flexibility, safety and raw material costs. The prepared ion conductors are difficult to accurately control the mechanical strength and conductivity, and cannot meet the needs of various ion electrical devices. Therefore, it is of great value to accurately control the polymer properties by designing polysulfide copolymer systems. Summary of the invention:

[0004] The present invention relates to a method for preparing a copolymer-modified polysulfide ion conductor, aiming at efficiently preparing a stretchable and self-repairing ion conductor.

[0005] The technical scheme of the present invention is: first, a certain amount of polysulfide is heated to melt or dissolved in a solution, and then a certain amount of ionic liquid, comonomer, catalyst, crosslinking agent, and lithium salt are added in sequence, and after a period of reaction, the polysulfide is formed in a mold to obtain a polysulfide ion conductor. The polysulfide and comonomer in the present invention can be polymerized under solvent-free conditions or in a room temperature solution environment. During the polymerization process, the molecular weight, flexibility, glass transition temperature, melting point and other properties of the ion conductor are synergistically regulated by variables such as catalysts and comonomers, the ionic conductivity of the ion conductor is regulated by lithium salts and ionic liquids, and the mechanical properties of the ion conductor are regulated by crosslinking agents.

[0006] A method for preparing a polysulfide ion conductor, characterized in that the method comprises the following steps:

[0007] (1) The method for solvent-free polymerization of polysulfide comprises the following steps: heating the polysulfide to above 70°C (preferably 120°C), adding a certain amount of comonomer and ionic liquid, wherein the molar ratio of polysulfide to comonomer and ionic liquid is 100:(5-95):(1-25) (preferably 100:90:5), then sequentially adding a catalyst and a cross-linking agent to the system, wherein the molar ratio of polysulfide to catalyst and cross-linking agent is 100:(0.01-10):(0.1-5), continuing heating and stirring for 5 min to 30 min, finally adding a certain amount of lithium salt, wherein the molar ratio of polysulfide to lithium salt is 100:(1-40), continuing stirring for 1 min to 5 min, and after forming a uniform and transparent solution, pouring it into a mold and cooling it at room temperature to obtain a polysulfide ion conductor.

[0008] (2) The method for room temperature solution polymerization of polysulfide comprises the following steps: dissolving polysulfide in a specific organic solvent (preferably dichloromethane) and adding a certain amount of comonomer and ionic liquid, wherein the concentration of polysulfide is 0.1 mol / L to 5 mol / L, and the molar ratio of polysulfide to comonomer and ionic liquid is 100:(5-95):(1-25) (preferably 100:90:5), and then adding a certain amount of catalyst, crosslinking agent and lithium salt to the system in sequence, wherein the molar ratio of polysulfide to catalyst, crosslinking agent and lithium salt is 100:(0.01-10):(0.1-5):(1-40), continuing stirring for 5 min to 60 min, removing the solvent by reduced pressure distillation, pouring into a mold, and cooling and drying at room temperature for 1 h to 2 h to further volatilize the residual solvent, thereby obtaining a polysulfide ion conductor.

[0009] The polysulfide of the present invention has the following structure:

[0010]

[0011] Among them, R1 is one or more of hydrogen, methyl, ethyl, n-propyl, isopropyl, trifluoromethyl, trifluoroethyl, and carboxyl; R2 is one or more of hydrogen, methyl, ethyl, n-propyl, isopropyl, trifluoromethyl, trifluoroethyl, hydroxyl, methoxy, ethoxy, n-propoxy, isopropoxy, trifluoroethoxy, octafluoropentyloxy, 2,2-dimethyl-1,3-dioxolane-4-methoxy, 1,3-dioxolane-4-methoxy, and phenoxy; the value of x is 2 to 8; the value of n is 0 to 2; and the polysulfide is one or more of I, II, and III.

[0012] The heating temperature of the polysulfide of the present invention is 70°C to 140°C, preferably 120°C.

[0013] The comonomer described in the present invention is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, itaconic acid, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, fumaric acid, dimethyl fumarate, dibutyl fumarate, monoethyl fumarate, cinnamic acid, sorbic acid, limonene, myrcene, divinylbenzene, diisopropenylbenzene, ethylene glycol vinyl ether, diethylene glycol vinyl ether, and triethylene glycol divinyl ether.

[0014] The ionic liquid described in the present invention is one or more of acrylic acid / choline chloride deep eutectic solvent, hydroxyethyl acrylate / choline chloride deep eutectic solvent, 1-vinyl-3-butyl imidazolium trifluoromethanesulfonyl imide salt, 1-ethyl-3-methyl imidazolium bis trifluoromethanesulfonyl imide salt, 1-butyl-3-methyl imidazolium bis trifluoromethanesulfonyl imide salt, N-methyl, butyl pyrrolidine bis trifluoromethanesulfonyl imide salt, 1-methyl-1-propyl pyrrolidine bis (trifluoromethanesulfonyl) imide salt, 1-ethyl-3-methyl imidazolium hexafluorophosphate, 1-hexyl-3-methyl imidazolium hexafluorophosphate, 1-butyl-3-methylpyridine hexafluorophosphate, 1-vinyl-3-ethyl imidazolium hexafluorophosphate, 1-vinyl-3-butyl imidazolium hexafluorophosphate, 1-ethyl-3-methyl imidazolium tetrafluoroborate, and 1-butyl-4-methylpyridine tetrafluoroborate. Under some conditions, the ionic liquid may not be used.

[0015] The catalyst described in the present invention is one or more of zinc oxide, ferric chloride, ferrous chloride, cupric chloride, zinc chloride, zinc stearate, zinc dimethyldithiocarbamate, iron diethyldithiocarbamate, copper diethyldithiocarbamate, copper diethyldithiocarbamate, nickel diethyldithiocarbamate, sodium diethyldithiocarbamate, and tetramethylthiuram disulfide.

[0016] The cross-linking agent described in the present invention is one or more of ferric chloride, aluminum chloride hexahydrate, zinc chloride, cupric chloride, calcium chloride, cadmium chloride, and nickel chloride. Under some conditions, no cross-linking agent may be used.

[0017] The lithium salt described in the present invention is one or more of lithium chloride, lithium fluoride, lithium oxalate, lithium difluorooxalatoborate, lithium tetraborate, lithium hexafluorophosphate, lithium hexafluorosilicate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium acetate, lithium bis(trifluoromethanesulfonyl imide), and lithium nitrate; preferably lithium chloride, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl imide).

[0018] The organic solvent described in the present invention is one or more of dichloromethane, tetrahydrofuran, acetone, methanol, ethanol, acetonitrile and chloroform, preferably dichloromethane.

[0019] Due to the adoption of the above technical solution, the present invention has the following advantages and effects:

[0020] (1) The present invention utilizes the rapid polymerization between polysulfide and comonomer to overcome the contradiction between complex structure and efficient manufacturing in polymer ion conductors. The present invention involves a rich variety of comonomers, and the generated polymers have diverse structures and adjustable properties, thereby achieving simultaneous improvement of mechanical properties and electrical conductivity in ion conductors, and can be applied to a variety of ion electrical devices.

[0021] (2) The preparation process of the present invention is simple and has high atomic utilization rate. The solvent-free method does not produce three wastes. The solution polymerization does not require heating and complex conditions. It meets the requirements of green chemistry and has practical industrial feasibility.

[0022] (3) The polysulfide ion conductors in the present invention have abundant dynamic covalent bonds (such as disulfide bonds) and non-covalent interactions (such as hydrogen bonds and lithium bonds). The ion conductors have certain self-healing properties, degradability and recyclability, which extend the service life and life cycle of the materials. Specific implementation method:

[0023] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with examples. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and the examples should not be regarded as limiting the scope of protection of the present invention.

[0024] Implementation Case 1

[0025] Preparation of polysulfide ion conductor by solvent-free polymerization: 20 g of thioctic acid powder and 1 g of sulfur powder were placed in a three-necked flask, heated in an oil bath at 140°C for about 10 min to completely melt the thioctic acid powder, and a certain amount of hydroxyethyl methacrylate (11.4 g), 1-vinyl-3-butyl imidazole hexafluorophosphate (0.2 g), iron diethyl dithiocarbamate (0.05 g), ferric chloride (0.31 g), and lithium chloride (0.82 g) were added in sequence, and the heating was stopped after stirring for 15 min. The liquid was poured into a mold and cooled to room temperature to obtain a fully solid polysulfide ion conductor. The mechanical properties, ionic conductivity, and self-healing efficiency test results of the obtained ion conductor are shown in the attached table. The ion conductor can be degraded in an aqueous sodium hydroxide solution (0.1 mol / L or higher concentration).

[0026] Implementation Case 2

[0027] The preparation process is generally the same as that of Example 1, except for the formula composition and reaction temperature. Take thioctic acid powder (20g) and place it in a three-necked flask, heat it in an oil bath at 120°C for about 10 minutes to completely melt the thioctic acid powder, and add a certain amount of hydroxyethyl acrylate (10g), 1-ethyl-3-methylimidazolium tetrafluoroborate (0.2g), zinc diethyldithiocarbamate (0.07g), aluminum chloride hexahydrate (0.23g), and lithium bistrifluoromethanesulfonyl imide (1.95g) in sequence, continue stirring for 15 minutes and then stop heating, pour the liquid into the mold and cool to room temperature to obtain a polysulfide ion conductor. The mechanical properties, ionic conductivity and self-healing efficiency test results of the obtained ion conductor are shown in the attached table. The ion conductor can be degraded in an aqueous sodium hydroxide solution (0.1mol / L or higher concentration) or an aqueous sodium bicarbonate solution (1mol / L or higher concentration).

[0028] Implementation Case 3

[0029] The preparation process is generally the same as that of Example 1, except for the formula composition and reaction temperature. Take methyl lipoate liquid (22g) and place it in a three-necked flask, heat it in a 40°C oil bath for about 10 minutes, and add a certain amount of triethylene glycol divinyl ether (5g), sodium diethyldithiocarbamate (0.03g), lithium bis(trifluoromethanesulfonyl imide) (1.95g), and lithium hexafluorophosphate (0.7g) in sequence. Continue stirring for 15 minutes and then stop heating. Pour the liquid into the mold and cool it to room temperature to obtain a polysulfide ion conductor. The mechanical properties, ionic conductivity and self-healing efficiency test results of the obtained ion conductor are shown in the attached table. The ion conductor can be degraded in sodium hydroxide aqueous solution (0.1mol / L or higher concentration), potassium carbonate aqueous solution (1mol / L or higher concentration), and sodium bicarbonate aqueous solution (1mol / L or higher concentration).

[0030] Implementation Case 4

[0031] Preparation of polysulfide ion conductor by room temperature solution polymerization: Take thioctic acid trifluoroethanol ester liquid (29g) and dissolve it in dichloromethane, add a certain amount of dimethyl itaconate (1.2g), sodium diethyldithiocarbamate (0.03g), lithium bis(trifluoromethanesulfonyl imide) (1.95g), lithium tetrafluoroborate (0.5g) in turn at room temperature, stir for 15min, remove the solvent by reduced pressure distillation at room temperature, pour the liquid into a mold for further volatilization and molding, and obtain a fully solid polysulfide ion conductor. The mechanical properties, ionic conductivity and self-healing efficiency test results of the obtained ion conductor are shown in the attached table. The ion conductor can be degraded in sodium hydroxide aqueous solution (0.1mol / L or higher concentration), potassium carbonate aqueous solution (1mol / L or higher concentration), and sodium bicarbonate aqueous solution (1mol / L or higher concentration).

[0032] Table 4 Performance of polysulfide ion conductors of Examples

[0033]

Claims

1. A method for preparing a polysulfide ion conductor, characterized in that: The method comprises the following steps: (1) The solvent-free polymerization method comprises the following steps: heating the polysulfide to a state above the molten state, and adding a certain amount of comonomer and ionic liquid, wherein the molar ratio of the polysulfide, the comonomer, and the ionic liquid is 100:(5-95):(1-25), then sequentially adding a catalyst and a cross-linking agent to the system, wherein the molar ratio of the polysulfide, the catalyst, and the cross-linking agent is 100:(0.01-10):(0.1-5), continuing heating and stirring for 5 min to 30 min, and finally adding a certain amount of lithium salt, wherein the molar ratio of the polysulfide to the lithium salt is 100:(5-40), continuing stirring for 1 min to 5 min, and after forming a uniform and transparent solution, pouring it into a mold and cooling it naturally to obtain a polysulfide ion conductor. (2) The method for room temperature solution polymerization of polysulfide comprises the following steps: dissolving polysulfide in a specific organic solvent (preferably dichloromethane) and adding a certain amount of comonomer and ionic liquid, wherein the concentration of polysulfide is 0.1 mol / L to 5 mol / L, and the molar ratio of polysulfide to comonomer and ionic liquid is 100:(5-95):(1-25) (preferably 100:90:5), and then adding a certain amount of catalyst, crosslinking agent and lithium salt to the system in sequence, wherein the molar ratio of polysulfide to catalyst, crosslinking agent and lithium salt is 100:(0.01-10):(0.1-5):(1-40), continuing stirring for 5 min to 60 min, removing the solvent by reduced pressure distillation, pouring into a mold, and cooling and drying at room temperature for 1 h to 2 h to further volatilize the residual solvent, thereby obtaining a polysulfide ion conductor.

2. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The polysulfide It has the following structure: Among them, R1 is one or more of hydrogen, methyl, ethyl, n-propyl, isopropyl, trifluoromethyl, trifluoroethyl, and carboxyl; R2 is one or more of hydrogen, methyl, ethyl, n-propyl, isopropyl, trifluoromethyl, trifluoroethyl, hydroxyl, methoxy, ethoxy, n-propoxy, isopropoxy, trifluoroethoxy, octafluoropentyloxy, 2,2-dimethyl-1,3-dioxolane-4-methoxy, 1,3-dioxolane-4-methoxy, and phenoxy; the value of x is 2 to 8; the value of n is 0 to 2; and the polysulfide is one or more of I, II, and III.

3. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The heating temperature of the polysulfide is 70°C to 140°C.

4. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The comonomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, itaconic acid, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, fumaric acid, dimethyl fumarate, dibutyl fumarate, monoethyl fumarate, cinnamic acid, sorbic acid, limonene, myrcene, divinylbenzene, diisopropenylbenzene, ethylene glycol vinyl ether, diethylene glycol vinyl ether, and triethylene glycol divinyl ether.

5. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The ionic liquid is one or more of acrylic acid / choline chloride low eutectic solvent, hydroxyethyl acrylate / choline chloride low eutectic solvent, 1-vinyl-3-butyl imidazolium trifluoromethanesulfonyl imide salt, 1-ethyl-3-methyl imidazolium bis trifluoromethanesulfonyl imide salt, 1-butyl-3-methyl imidazolium bis trifluoromethanesulfonyl imide salt, N-methyl, butyl pyrrolidine bis trifluoromethanesulfonyl imide salt, 1-methyl-1-propyl pyrrolidine bis (trifluoromethanesulfonyl) imide salt, 1-ethyl-3-methyl imidazolium hexafluorophosphate, 1-hexyl-3-methyl imidazolium hexafluorophosphate, 1-butyl-3-methylpyridine hexafluorophosphate, 1-vinyl-3-ethyl imidazolium hexafluorophosphate, 1-vinyl-3-butyl imidazolium hexafluorophosphate, 1-ethyl-3-methyl imidazolium tetrafluoroborate, and 1-butyl-4-methylpyridine tetrafluoroborate. Under some conditions, ionic liquids may not be used.

6. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The catalyst is one or more of zinc oxide, ferric chloride, ferrous chloride, cupric chloride, zinc chloride, zinc stearate, zinc dimethyldithiocarbamate, iron diethyldithiocarbamate, copper diethyldithiocarbamate, copper diethyldithiocarbamate, nickel diethyldithiocarbamate, sodium diethyldithiocarbamate, and tetramethylthiuram disulfide.

7. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The cross-linking agent is one or more of ferric chloride, aluminum chloride hexahydrate, zinc chloride, cupric chloride, calcium chloride, cadmium chloride, and nickel chloride. Under some conditions, no cross-linking agent may be used.

8. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The lithium salt is one or more of lithium chloride, lithium fluoride, lithium oxalate, lithium difluorooxalatoborate, lithium tetraborate, lithium hexafluorophosphate, lithium hexafluorosilicate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium acetate, lithium bis(trifluoromethanesulfonyl imide), and lithium nitrate.

9. The method for preparing a polysulfide ion conductor according to claim 1, characterized in that: The organic solvent is one or more of dichloromethane, tetrahydrofuran, acetone, methanol, ethanol, acetonitrile and chloroform.

Citation Information

Cited By

  • Lignin-based self-repairing binder as well as preparation method and application thereof

    CN120904815A